IMPLEMENTATION OF LEADERSHIP STYLE IN IMPROVEMENT POLICE PERFORMANCE SPECIAL CRIMINAL RESEARCH DIRECTORATE SUBDIT IV/TIPIDTER OF CENTRAL KALTENG REGIONAL POLICE IN PALANGKARAYA - Muhammad Subair; Hary Soegiri (INFOKUM, 2020)
This study aims to answer the question: (1) implementation of leadership style implementation (2) Performance of police members (3) implementation of leadership style implementation to improve the performance of police members. With research location in Subdit IV / Tipidter Palangkaraya Central Kalimantan Police. This research uses descriptive qualitative method. Data obtained through interview techniques, documentation and observation. From the results of this research it is known that: (1) Implementation of leadership style implementation goes well. (2) The performance of police officers is excellent. (3) The link between the implementation of leadership style implementation to improve the performance of police members in Subdit IV / Tipidter Palangkaraya Polda Central Kalimantan is very closely, judging from the findings of researchers in the field that the implementation of good leadership style implementation of The Head of Sub-District IV / Tipidter Palangkaraya Central Kalimantan Police and Kanit of each unit is related to the improvement of the performance of police members in the unit. The suggestions that researchers put forward in this study are: (1) Implementation of leadership implementation in Subdit IV / Tipidter Palangkaraya Polda Central Kalimantan to be maintained and developed in accordance with the situation that will continue to develop. (2) The good performance of the members in Subdit IV / Tipidter Palangkaraya Polda Central Kalimantan continues to be forged until it eventually becomes a habit and personality of each member. (3) Reward and punishment in Subdit IV / Tipidter Palangkaraya Polda Central Kalimantan to be improved so that it becomes an additional motivation in improving its performance .